UV Laser‐Induced Polyimide‐to‐Graphene Conversion: Modeling, Fabrication, and Application. Issue 10 (26th April 2019) - Chen, Yun; Long, Junyu; Zhou, Shuang; Shi, Dachuang; Huang, Yan; Chen, Xin; Gao, Jian; Zhao, Ni; Wong, Ching‐Ping
Abstract: In the past decade, graphene has shown great value in both fundamental sciences and practical applications. In spite of the intense research efforts on achieving chemical‐free, low‐temperature processing of high‐quality graphene, cost‐effective synthetic methods to directly fabricate graphene sheets on a substrate are still lacking. Laser‐induced graphene (LIG) is a recently developed method to directly form graphene from carbon‐rich materials. In this work, combined are theoretical and experimental approaches to systematically investigate the light‐material interactions in LIG fabrication processes. First, developed is a molecular dynamics model to disclose the transient formation process of LIG and identified are the critical parameters that govern this process. Following the theoretical prediction, developed is a system to utilize a picosecond UV laser to directly fabricate graphene from polyimide films at room temperature and under atmospheric pressure. After investigating the effects of the laser processing parameters on the LIG quality and subsequent processing optimization, it is experimentally demonstrated that picosecond UV laser processing can be used to prepare high‐quality LIG. With the newly developed LIG, fabricated is a high‐sensitive proximity sensor. Abstract : The light‐material interactions in laser‐induced graphene (LIG) fabrication processes are systematically investigated. The critical parameters that govern this process are identified by modeling. And picosecond UV laser processing is experimentally demonstrated that can also be used to prepare high‐quality LIG from polyimide at ambient conditions. To demonstrate the potential application, a high‐sensitive proximity sensor is fabricated.